Robert Edwin Peary (1856-1920) - Weems, John Edward (ARCTIC, 1982)
"I must have fame," young Robert Edwin Peary told his mother more than once. In the dwindling nineteenth century, large areas of the planet still had not been visited by man. After much deliberation, Peary made his choice: he would become an arctic explorer, would be the first man to reach the North Pole. . About 1885 Peary's interest in the North was rekindled. He began poring over voluminous reports of arctic explorers during his free hours. On 13 October of that year, he wrote himself a memorandum (which I found in 1962 in his own voluminous papers) that the time had come "for an entire change in the expeditionary organization of Arctic research." Instead of utilizing large parties and several ships, he wrote, he would have a small group relying on Eskimo assistance. He had not been to the Arctic then, but the method he outlined would eventually bring him success. From 1886 to 1909 Peary devoted himself to planning and leading eight arctic expeditions - one of them of four years' duration. With increasing difficulty, he obtained leaves of absence from the Navy, raised his own money, recruited his own men, made his own rules-and expected strict compliance. . The early desire for fame became an obsession to reach a goal. During years of exploration Peary mapped unknown lands and showed Greenland to be an island, but he did not get to the North Pole. To him this meant failure. Finally, he succeeded, at the age of 52-a wiry, auburn-haired, mustached man who could still hold his six-foot frame erect, but whose drawn, ruddy face and squinting eyes indicated hard experience. On 1 April 1909, he said good-bye to the last of four compact supporting parties that had accompanied him across the treacherous, ever-shifting ice of the Arctic Ocean. Then, with a black assistant, Matthew Henson, four Eskimos, five sledges, and 40 dogs, he struggled across more floating ice and reached the Pole five days later, according to his navigation, only to return to civilization and learn that Dr. Frederick A. Cook, a former Peary ...